Media pembelajaran infografis (statis, animasi, dan interaktif) dan dampaknya terhadap keterampilan berpikir kreatif dalam pembelajaran biologi - Nur Alamsyah; Adnan; Muhiddin Palennari (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to compare the effectiveness of three types of infographics, namely static, animated, and interactive, on students' creative thinking skills in biology learning on the human circulatory system. The research method used was a quasi-experimental with a pretest-posttest control group design, involving 144 grade XI students at SMA Negeri 3 Takalar who were divided into four classes: three experimental classes and one control class. The instrument used was a creative thinking skills essay test developed based on Guilford indicators (fluency, flexibility, originality, and elaboration). Data analysis was carried out using the ANCOVA test and LSD follow-up test. The results showed a significant difference between classes (F = 582.693; p < 0.05). The average value of estimated marginal means showed that interactive infographics had the greatest influence (86.89), followed by static infographics (84.27), animation (81.53), and handouts (74.18). Learning using interactive infographics provides navigation autonomy and encourages higher cognitive engagement, making it more effective in developing students' creative thinking skills. This research emphasizes the importance of utilizing interactive media in biology learning to optimally develop creative thinking skills